Treatment of X-linked lymphoproliferative disease (Duncan disease) with high-dose methylprednisolone and etoposide (VP-16) - Gürgey, Aytemiz; Şaylı, Tülin; Kara, Abdurrahman; Kale, Gülsev; Berkel, İzzet (The Turkish Journal of Pediatrics, 1996)
A five-year-old boy in the acute phase of X-linked lymphoproliferative (XLP) syndrome (Duncan disease) with high fever and hepatosplenomegaly was treated successfully with high-dose methylprednisolone and VP-16 for 15 months. He had been alive for four years after diagnosis as of this writing. We recommend high-dose methylprednisolone and VP-16 in patients with XLP who have to wait for a suitable donor before bone marrow transplantation.
Keywords: X-linked lymphoproliferative disease; high-dose methylprednisolone; VP-16; treatment